The profile and support needs of parents in paediatric palliative care: comparing cancer and non-cancer groups - Samar M. Aoun; Fenella J. Gill; Marianne B. Phillips; Suzanne Momber; Lisa Cuddeford; Renee Deleuil; Roswitha Stegmann; Denise Howting; Maureen E. Lyon (Palliative Care and Social Practice, 2020)
Background: Parents of children with life-limiting illnesses experience considerable burden and distress, yet few interventions have targeted their well-being. Objectives: Evaluate the use and feasibility of the Paediatric Carer Support Needs Assessment Tool (pCSNAT) in assessing and addressing parents’ needs caring for cancer and non-cancer conditions. Carer well-being outcomes were also tested. Methods: A non-randomised prospective intervention pilot study. Twenty-eight parents (out of 42 approached) and 5 health professionals working in paediatric palliative care services in Western Australia (2018–2019) completed the pilot study. Results: Two-thirds of eligible parents completed the study. The highest support needs included having time for yourself; practical help in the home; knowing what to expect in the future; financial, legal or work issues; and knowing who to contact if you are concerned. Almost all needs were considerably more pronounced for the non-cancer group. The pCSNAT seemed feasible and outcomes demonstrated a tendency to improve. Conclusion: Using the pCSNAT provided a concise and comprehensive ‘one stop shop’ for health professionals to evaluate difficulties encountered by parents. The disadvantages reported by the non-cancer group warrant increased attention. Paediatric palliative care should adopt routine assessment of parents’ support needs to anticipate early and tailored supports including partnerships with the community.